Wypędzenie jezuitów z Imperium Rosyjskiego na podstawie fragmentów "Wygnańca z Białej Rusi" Jana Galicza - Demkowicz, Agata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
This publication concerns Jan Galicz’s memoirs devoted to the expulsion of Jesuits from Russia. They were written in the form similar to a journey diary. It means that the diarist did not respect all the principles of the genre. Galicz’s narrative was divided into days but he not always gave the precise date with the day of the week to the descriptions and events. He was also not consequent in using markings like ‘in the morning’, ‘in the afternoon’, ‘after dinner’, characteristic for the daily narrative. Their usage would significantly influence the preservation of chronology of events. The Jesuit from Belarus only from time to time uses expressions like ‘after lunch’, ‘in the afternoon’, ‘at five o’clock’. Galicz did not pay attention to systematic daily narrative which constitutes a crucial indication of the diary genre. The cited excerpts from the diaries left by Galicz prove that his diaries do not belong to the group of distinguished works on the background of the output of Polish Enlightenment period. However, he makes reference to very important events in the history of the order. Moreover, he describes them from the perspective of their direct witness and participant.
Expulsion of Jesuits from Russian empire based on excerpts from “Wygnaniec z Białej Rusi” (”Exile from White Russia”) by Jan Galicz
Keywords: Galicz Jan; oświecenie; literatura jezuicka; pamiętniki polskie - XIX w.; diariusz podróży; edytorstwo dzieł literackich